Diversidade genética em populações de Candidatus Liberibacter asiaticus determinada por marcadores SSR - Paula, Larissa Bonevaes de [UNESP] (2015)
Citrus huanglongbing (HLB) disease emerged as a primary threat for citrus production worldwide, associated with the phloem and vectored (Diaphorina citri) limited - bacterium Candidatus Liberibacter asiaticus (Las). In Brazil, HLB was first reported in 2004 and quickly spread for all geographic regions of the States of Sao Paulo (SP), Parana (PR) and Minas Gerais (MG). However, information about genetic diversity of this bacterium is poorly known. Here we tested the hypothesis H0: different geographic regions and citrus species have no influence on genetic diversity of Las populations in Brazil. To test this hypothesis, total DNA from 199 samples from citrus plants with symptoms of HLB was amplified by 9 sets of forwardfluorescent microsatellites primers. Moderately low levels of genetic diversity (HNei = 0,11 to 0,26) were observed through all populations. By Wright's F-statistics (FST), no statistic difference was observed among Las populations from all the seven previously subdivided geographic regions of SP and MG (FST <0,095). But significant FST values (0,118 to 0,191) were obtained for Las population from PR compared to SP and MG. On the other hand, highest and significant values for FST index (0,275 to 0,445) were observed comparing Las populations from sweet orange trees from SP, MG, and PR and the populations from different citrus species grown at the Southeast region of SP. By Bayesian statistics and principal coordinate analysis all isolates studied were clustered in three genetically different populations: 1. a group that includes all strains from SP regions and MG, 2. A second composed only by Las strains from PR, and 3. a third where strains from different citrus species were grouped. In conclusion, after 10 years of the HLB first report in Brazil, that genetically homogeneous populations of Las infecting sweet orange are present at different geographic regions sampled, with the exception of the populations ...